The First V4 Summer School in Economic History, Prague, 2023 - Doležalová, Antonie (Historical Studies on Central Europe, 2023)
In the last week of August 2023 (27 Augustus – 2 September), the first V4 Summer School in Economic History was held in Prague. It was organized by the Institute of History of the Czech Academy of Sciences in cooperation with the Slovak Academy of Sciences, Bratislava, Eötvös Loránd University, Budapest, and the University of Warsaw. The event was financially supported by the Visegrad Fund. The long-term target of the Ph.D. Summer School in Economic History was to incorporate the V4 historiographies of economic history into international networks. It intended to encourage the young generation of economic historians to enter the international scene and participate in an open academic discussion.